POLA-POLA PENGGUNAAN KATA ISIM DAN FI'IL DALAM AL-QUR’AN - Wahidi, Ridhoul (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2014)
The aim of this paper is to examine the use of the word isim and fi’il in the Qur'an. This research method is to process data related to the books of fi’il and isim that have relevance aspect to the language of the Qur’an. Among the results of this study are: the nature of isim is not only a noun, but also adjectives, state, pronouns, appoint, name, and mashdar. Isim divided into seven categories there are (mudzakkar, muannats, simplex, mutsanna, and plural, and ma'rifat nakirah, munsharif and ghair munsharif, maqshur and manqush, jamid and musytaq, mu'rab and mabni). While fi’il consists of three parts, (simple past fi’il madhi, simple present fi’il mudhari ', and simple future fi’il amr). DOI: 10.15408/a.v1i2.1143